Il secolarismo all’ombra dei minareti: il principio costituzionale di laicità nella Turchia moderna e contemporanea (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Premessa introduttiva - 2. La Türkiye Cumhuriyeti tra eredità islamica e legittimazione internazionale - 3. La laicità dello Stato: il fondamento della nuova identità nazionale - 4. Le forze armate e la Corte costituzionale: i ‘custodi’ della laiklik - 5. La parabola dell’AKP: dall’impulso riformista alla recente involuzione autoritaria - 6. Le implicazioni giuridiche del fallito golpe del 2016.Secularism in the shadow of the minarets: the constitutional principle of secularism in modern and contemporary TurkeyABSTRACT: The present essay deals with the so-called ‘laiklik’, namely the Kemalist understanding of the constitutional principle of secularism implemented in the Turkish legal framework over the last century. The analysis takes as a starting point the establishment of the modern Republic of Turkey and focuses firstly on the staunch protection of secularism by its traditional ‘guardians’ (i.e. the army and the Constitutional Court). In particular, it is argued that the rhetoric of secularism has been exploited by the ruling élites with the aim to curb religious, cultural and political pluralism. Subsequently, the paper investigates the controversial policies adopted by the AKP - the moderate pro-Islamic party in power uninterruptedly since 2002 - and the rule of law crisis recently occurred in the country. In this regard, the author eventually seeks to assess the aftermath of the coup attempt failed in July 2016, by giving special attention to its short and long-term implications in the light of Turkish secularism.